Dimensional Analysis via an Electromagnetically-Oriented Set of Fundamental Dimensions - Rushdi, Ali; Rushdi, Mostafa (Journal of King Abdulaziz University: Engineering Sciences, 2022)
Abstract. This paper describes the electromagnetically-oriented dimensional basis that is based on the reference dimensions of Length ( ), Time (T), Electric Current ( ), and Electric Potential ( ). We utilize this basis in the matrix solution of dimensional-analysis (DA) problems involving mainly electromagnetic quantities. Representations of electromagnetic quantities in the basis (compared with the standard basis that uses Mass ( ) instead of Potential ( )) are more informative, much simpler, and have salient duality features. Moreover, DA computations of electromagnetic problems via the Gauss-Jordan algorithm in the basis are more efficient, much less error prone, and quicker to detect linear dependencies in the dimensional equations. Both details and advantages of the proposed method are explored via demonstrative examples, which are of obvious significance in the learning and teaching of electromagnetism.